20 days in Mariupol [videorecording (DVD)] - Chernov, Mstyslav; Chernov, Mstyslav (PBS Distribution, 2023)
As the Russian invasion begins, a team of Ukrainian journalists trapped in the besieged city of Mariupol struggle to continue their work documenting the war's atrocities.